Association of C677T and A1298C MTHFR Polymorphisms and Fluoropyrimidine-induced Toxicity in Mestizo Patients With Metastatic Colorectal Cancer - Ramos Esquivel, Allan Eduardo (2020)
Background/aim: Enzymatic variants involved in fluoropyrimidine metabolism have been associated with adverse events (AEs). We assessed the association between C677T (rs1801133) and A1298 (rs1801131) methylenetetrahydrofolate reductase (MTHFR) polymorphisms and AEs in patients with first-line fluoropyrimidine-based chemotherapy. Patients and methods: Fifty patients with metastatic colorectal cancer were prospectively followed-up during the first 4 cycles of fluoropyrimidine-based treatment to assess AEs. Germline DNA was analyzed to determine the C677T and A1298C MTHFR polymorphisms. The associations between MTHFR polymorphisms and toxicity were examined. Results: Individuals carrying at least one mutant allele of the MTHFR C677T polymorphism had increased risk to experience anemia (OR=1.69, 95% CI=1.13-2.53, p=0.005), neutropenia (OR=2.27, 95% CI=1.47-3.42, p<0.001) thrombocytopenia (OR=1.91, 95% CI=1.30-2.70, p<0.001), neuropathy (OR=1.77, 95% CI=1.16-2.70, p=0.02), diarrhea (OR=1.69, 95% CI=1.13-2.53, p=0.005), and hand-foot syndrome (OR=1.56, 95% CI=1.08-2.27, p=0.013), compared to patients carrying the wild type alleles. The presence of the mutant allele C of the MTHFR A1298C polymorphism was associated with increased risk of anemia (OR=2.75, 95% CI=1.01-7.48, p=0.02) and thrombocytopenia (OR=3.14, 95% CI=1.01-9.78, p=0.03); however, the prevalence of this allele in the sample was quite low (20%). Conclusion: MTHFR C677T and A1298C polymorphisms predicted toxicity in a subset of Mestizo patients with colorectal adenocarcinoma.